Analisis Tingkat Pendidikan Orangtua Terhadap Motivasi Belajar Fisika Siswa Sekolah Menengah di Kecamatan Kontukowuna - Nuraida Saudi; Halmuniati Halmuniati; Nilawati Ute (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The purpose of the study was to see how much influence the level of parental education had on students’ motivation to learn physics in two secondary schools in Kontukowuna District, Muna Regency. This research is quantitative research, with the population used is all students of class XI science at SMAN 1 Kontukowuna and all students of class VIII at SMPN 1 Kontukowuna. The sampling technique used was non-probability sampling with the category of random sampling, where the samples used were 28 people for high school and 30 people for junior high school. The data analysis technique uses simple linear regression analysis through SPSS 16. Data analysis using the t-test regression equation shows a significant influence of the students' parents' education level on their motivation to learn physics, 94.1% for SMAN 1 Kontukowuna and SMPN 1 Kontukowuna with a significant effect of 84.8%. From the results obtained, it can be concluded that there is an influence of the level of parental education on students' learning motivation